Hubungan antara Problem Focused Coping dengan Kepatuhan pada Mahasiswa Baru Universitas Teknologi Sumbawa - Aisyah, Aisyah; Insan, Imammul (Indo-MathEdu Intellectuals Journal, 2025)
Compliance that occurs in new students occurs because of the problem focused coping that good students have and vice versa. This research aims to determine the relationship between problem focused coping and compliance in new students at Sumbawa University of Technology. The approach used in this research is a quantitative type of correlation with product moment correlation data analysis techniques. The data collection technique uses a questionnaire. The results of the research show that there is a positive and significant relationship between problem focused coping and compliance among new students at Sumbawa University of Technology with a correlation coefficient between the two variables of r = 0.791: p = 0.000 (p < 0.005) which means the higher the problem focused coping, the higher high level of compliance among new students at Sumbawa University of Technology. Likewise, vice versa, the lower the problem focused coping, the lower the compliance of new students at Sumbawa University of Technology.